Endothelial cell activation and glycocalyx shedding - potential as biomarkers in patients with lupus nephritis - Yung, Susan; Chan, Tak Mao (Frontiers in Immunology, 2023)
Lupus nephritis (LN) is a common and severe manifestation of systemic lupus erythematosus and an important cause of acute and chronic kidney injury. Early diagnosis of LN and preventing relapses are key to preserving renal reserve. However, due to the complexity and heterogeneity of the disease, clinical management remains challenging. Kidney biopsy remains the gold standard for confirming the diagnosis of LN and subsequent assessment of kidney histopathology, but it is invasive and cannot be repeated frequently. Current clinical indicators of kidney function such as proteinuria and serum creatinine level are non-specific and do not accurately reflect histopathological changes, while anti-dsDNA antibody and C3 levels reflect immunological status but not kidney injury. Identification of novel and specific biomarkers for LN is prerequisite to improve management. Renal function deterioration is associated with changes in the endothelial glycocalyx, a delicate gel-like layer located at the interface between the endothelium and bloodstream. Inflammation induces endothelial cell activation and shedding of glycocalyx constituents into the circulation. This review discusses the potential role of soluble glycocalyx components as biomarkers of active LN, especially in patients in whom conventional serological and biochemical markers do not appear helpful.